1992
DOI: 10.1016/1044-0305(92)87042-w
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of 1- and 3-methoxypropene ions another part of the C4H8O+•potential energy surface

Abstract: The fragmentation mechanisms of metastable ionized 1- and 3-methoxypropene have been examined in detail by using ionization and appearance energy measurements, metastable ion and collisional activation mass spectra, and a variety of isotopically labeled molecules. These metastable C4H8O(+•) ions fragment by loss of H; CH3, and H2CO, and the experimental observations allowed the construction of the potential energy diagram which describes their interconversion and the participation of four other distonic and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Studies of metastable ionised allyl methyl ether 34,35 and the four isomeric butenyl methyl ethers 36 shed further light on the chemistry of these radical cations. From experiments with 2 H-labelled analogues of C 3 H 5 OCH 3…”
Section: (B)3233mentioning
confidence: 99%
“…Studies of metastable ionised allyl methyl ether 34,35 and the four isomeric butenyl methyl ethers 36 shed further light on the chemistry of these radical cations. From experiments with 2 H-labelled analogues of C 3 H 5 OCH 3…”
Section: (B)3233mentioning
confidence: 99%
“…In fact, to reveal the reaction mechanisms for the unimolecular dissociation of 1, it is necessary to thoroughly explore the potential energy surface for all possible fragmentation channels. [13][14][15] In this study, therefore, we theoretically examine the photodissociation process of 1 with the competitive reaction product channels aer onephoton excitation from the cationic ground state prepared by a (2 + 1) REMPI scheme. The quantum chemical calculation alongside experimental observations will further provide insights to the photodissociation dynamics of 1 in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…Reference spectra of ions of known structure are also given in these Tables. The structures of these ions (13)(14)(15)(16)(17)(18), which were generated by ionisation and alkyl radical loss from secondary and tertiary alkenyl methyl ethers (8)(9)(10)(11)(12) , as shown by their similar CID spectra, which are distinct from that of the isomeric ion, 18, Table 3.…”
Section: Structure Of the [M -Alkyl] + Ions Formed By γ-Cleavagementioning
confidence: 99%
“…16,17 Further investigation of higher homologues showed that loss of a methyl radical from ionised allylic alkenyl methyl ethers containing β-and γ-methyl substituents was consistent with a general mechanism involving formation and γ-cleavage of an ionised enol ether. Thus, 14 These results were inconsistent with expulsion of a β-alkyl group by β-cleavage of the relevant DI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation